Prostate brachytherapy seed migration to the right renal artery due to right‐to‐left shunting across a patent foramen ovale - Makoto Nakiri; Kosuke Ueda; Ryuji Hoshino; Naoki Ito; Hirofumi Kurose; Shoichiro Nohara; Koichiro Muraki; Chikayuki Hattori; Etsuyo Ogo; Tsukasa Igawa (IJU Case Reports, 2024)
Introduction The seeds used in brachytherapy for prostate cancer may migrate through the surrounding venous plexus to other sites in the body, most commonly to the pulmonary vasculature. Case presentation A 78‐year‐old Japanese man received iodine‐125 low‐dose‐rate prostate brachytherapy. Computed tomography revealed that one seed had migrated to the right kidney. No seed was observed in the ureter upon ureteroscopy. Transesophageal echocardiography confirmed a right‐to‐left shunt due to a patent foramen ovale, suggesting that the seed had migrated into the right renal artery. Three years after treatment, no recurrence of prostate cancer and no adverse events due to seed migration or due to the patent foramen ovale occurred. Conclusion Arteriovenous malformations and a right‐to‐left shunt should be suspected if a brachytherapy seed has migrated to an artery of the systemic circulatory system.